Advances in succinic acid production: the enhancement of CO2 fixation for the carbon sequestration benefits - Lin, Fanzhen; Li, Wenwei; Wang, Dan; Hu, Ge; Qin, Zhao; Xia, Xue; Hu, Lin; Liu, Xuemei; Luo, Ruoshi (Frontiers in Bioengineering and Biotechnology, 2024)
Succinic acid (SA), one of the 12 top platform chemicals produced from biomass, is a precursor of various high value-added derivatives. Specially, 1 mol CO2 is assimilated in 1 mol SA biosynthetic route under anaerobic conditions, which helps to achieve carbon reduction goals. In this review, methods for enhanced CO2 fixation in SA production and utilization of waste biomass for SA production are reviewed. Bioelectrochemical and bioreactor coupling systems constructed with off-gas reutilization to capture CO2 more efficiently were highlighted. In addition, the techno-economic analysis and carbon sequestration benefits for the synthesis of bio-based SA from CO2 and waste biomass are analyzed. Finally, a droplet microfluidics-based high-throughput screening technique applied to the future bioproduction of SA is proposed as a promising approach.